Development of student worksheets based on STEM and religion in digestive system materials - Zuhair Abdullah; Tresia Istiqomah; Ratna Sari (STKIP Persada Khatulistiwa Sintang, 2023)
Integration of STEM (Science, Technology, Engineering, and Mathematics) with religious values in learning is important to do so that material can be conveyed more thoroughly in aspects of students’ lives. So, this study aims to: first, produce and describe STEM-Religion-based worksheets on digestive system materials; second determine the feasibility level of the worksheet developed. This research method uses research and development methods using Analysis Design, Development, Implementation, and Evaluation (ADDIE) model. The results of this study are: first, elements of science were developed in the matter of nutritional content, elements of technology were developed in material processing technology and food safety, elements of engineering were developed in the process of designing healthy menus, mathematical elements were developed by calculating calorie needs and food preparation costs. The addition of religion element is divided into 3 sub-topics, namely the topic of the concept of halalan thayyiban food, eating and drinking etiquette according to Islam, and eating portions in Islam. Second, the average product assessment by validators on a scale of five obtained a score of 4.2 with a very good category, so it can be concluded that the developed worksheet is feasible to use.